The cultures of Maimonideanism : new approaches to the history of Jewish thought - Robinson, James T., 1965- (Supplements to The Journal of Jewish Thought and Philosophy, 2009)
In the history of Jewish thought, no individual scholar has exercised more influence than Maimonides (1138-1204) - philosopher and physician, legal scholar and communal leader. This collection of papers, originating at the 2007 EAJS colloquium, places primary emphasis on this influence - not on Maimonides himself but the many movements he inspired. Using Maimonideanism as an interpretive lens, the authors of this volume - representing a variety of fields and disciplines - develop new approaches to and fresh perspectives on the peculiar dynamic of Judaism and philosophy. Focusing on social and cultural processes as well as philosophical ideas and arguments, they point toward an original reconceptualization of Jewish thought.